Deltamides and Croconamides: Expanding the Range of Dual H‐bond Donors for Selective Anion Recognition. Issue 5 (15th December 2017) - Zwicker, Vincent E.; Yuen, Karen K. Y.; Smith, David G.; Ho, Junming; Qin, Lei; Turner, Peter; Jolliffe, Katrina A.
Abstract: Dual H‐bond donors are widely used as recognition motifs in anion receptors. We report the synthesis of a library of dual H‐bond receptors, incorporating the deltic and croconic acid derivatives, termed deltamides and croconamides, respectively, and a comparison of their anion binding affinities (for monovalent species) and Brønsted acidities to those of the well‐established urea and squaramide dual H‐bond donor motifs. For dual H‐bonding cores with identical substituents, the trend in Brønsted acidity is croconamides>squaramides>deltamides>ureas, with the croconamides found to be 10–15 p K a units more acidic than the corresponding ureas. In contrast to the trends displayed by ureas, deltamides and squaramides, N, N′ ‐dialkyl croconamides displayed higher binding affinity to chloride than the N, N′ ‐diaryl derivatives, which was attributed to partial deprotonation of the N, N′ ‐diaryl derivatives at neutral pH. A number of differences in anion binding selectivity were observed upon comparison of the dual H‐bond cores. Whereas the squaramides display similar affinity for both chloride and acetate ions, the ureas have significantly higher affinity for acetate than chloride ions and the deltamides display higher affinity for dihydrogenphosphate ions than other oxoanions or halides. These inherent differences in binding affinity could be exploited in the design of anion receptors with improved ability to discriminate between monovalent anions. Abstract : Croconamides spotted in the delta ! Bite‐angle and Brønsted acidity control anion binding affinity and selectivity by amides from the oxo‐carbon family.